KLASIFIKASI EMOSI TOKOH KAZUMA DALAM DRAMA TODOME NO KISS KARYA SUGAWARA SHINTARO - Angelsita Mogot; Wayan Nurita (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2025)
This study is a qualitative descriptive study using a literary psychology approach that examines the classification of emotions possessed by the character Kazuma in the Japanese television drama, Todome No Kiss by Sugawara Shintaro. This study aims to describe the emotional classification of Kazuma's character which displays an unnatural psychological side. As for the results of this study, it can be seen that the character Kazuma in the drama Todome No Kiss has 5 classifications of emotions from 7 classifications of emotions that exist according to David Krech's theory.